2013
DOI: 10.3382/ps.2013-03321
|View full text |Cite
|
Sign up to set email alerts
|

A 5-year retrospective report of Gallibacterium anatis and Pasteurella multocida isolates from chickens in Mississippi

Abstract: A 5-yr retrospective study (November 2006-December 2011) was conducted to determine the isolation frequency of Pasteurella multocida and Gallibacterium anatis and their antibiograms from chickens submitted to the Mississippi Poultry Research and Diagnostic Laboratory. The number of isolations of G. anatis increased over the last 5 yr in broiler and broiler breeder type chickens. For P. multocida, the number of isolations increased from 2006 to 2010, but decreased through 2011 with all isolations being from boi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 20 publications
4
37
0
Order By: Relevance
“…On the other hand all isolates were complete resistant to oxytetracyclin and doxycycline. This result agreed with Bojesen et al (2011), who noted that 97%of field strains were resistant to tetracycline, also agreed with Dewhirst et al, (1993); Janda (2011) and Jones et al, (2013).Other result optained by Bojesen et al(2007) who recorded that all isolates were sensitive to amoxicillin-calivulinic acid and El Bestawy 2014 who recorded that they resistant to sulpha. Trimethoprim.The differences in resistance patterns are widely due to factors which include differences in geographical locations, particular bacteria species involved, the animal production systems, the extent to which antibiotics are used, sampling techniques and period of sampling (Adzitey et al,2015).…”
Section: Molecular Characterization Of Virulence Genes Of Ganatis:-supporting
confidence: 84%
“…On the other hand all isolates were complete resistant to oxytetracyclin and doxycycline. This result agreed with Bojesen et al (2011), who noted that 97%of field strains were resistant to tetracycline, also agreed with Dewhirst et al, (1993); Janda (2011) and Jones et al, (2013).Other result optained by Bojesen et al(2007) who recorded that all isolates were sensitive to amoxicillin-calivulinic acid and El Bestawy 2014 who recorded that they resistant to sulpha. Trimethoprim.The differences in resistance patterns are widely due to factors which include differences in geographical locations, particular bacteria species involved, the animal production systems, the extent to which antibiotics are used, sampling techniques and period of sampling (Adzitey et al,2015).…”
Section: Molecular Characterization Of Virulence Genes Of Ganatis:-supporting
confidence: 84%
“…are involved in causing septicemia (Fisher et al 1998;Ewers et al 2004;Abdul-Aziz et al 2016). In recent past, several reports of clinical cases in avian and experimental studies in chickens revealed Gallibacterium anatis to be an important bacterial pathogen associated with septicemia (Bojesen et al 2004;Neubauer et al 2009;Jones et al 2013;Paudel et al 2013;Elbestawy 2014;Paudel, Liebhart, Aurich, et al 2014;Paudel et al 2015;Persson & Bojesen 2015).…”
Section: Introductionmentioning
confidence: 99%
“…anatis, particularly the hemolytica biovar, reported to cause oophoritis, salpingitis, peritonitis, perihepatitis, liver necrosis, pericarditis, air sacculitis, tracheitis, enteritis and septicemia in chickens (Bisgaard 1977;Mushin et al 1980;Shaw et al 1990;Mirle et al 1991;Bojesen et al 2004;Neubauer et al 2009;Paudel et al 2013). In egg-laying hens, reproductive organs are chiefly affected, and this bacterium produces lesions including hemorrhagic oophoritis and rupture of ovarian follicles (Hacking & Pettit 1974;Jones et al 1981;Neubauer et al 2009;Jones et al 2013;. G. anatis has been considered as a primary organism associated with lowered egg production, leading to 8-10% yield reduction and found to cause mortality up to 73% in experimentally immunosuppressed layer chickens (Mirle et al 1991;Jordan et al 2005;Neubauer et al 2009;Shapiro et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In affected animals, G. anatis is often co-isolated together with other poultry pathogens, which previously left its clinical relevance as a matter of controversy [4,6]. Several studies have however shown that G. anatis infections correlate with decreased egg production and increased mortality in laying hens [7][8][9], leading to the widespread recognition of G. anatis as an emerging threat to chicken egg and meat production.…”
Section: Introductionmentioning
confidence: 99%